2021
DOI: 10.1002/pol.20210714
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation in aqueous solutions of poly(ethylene glycol) methacrylate homopolymers

Abstract: Here, the liquid–liquid phase separation (LLPS) in aqueous solutions containing poly(ethylene glycol) (PEG) methacrylate homopolymers is reported for the first time. In this study, the thermoresponse of concentrated solutions of DEGMA60 (two ethylene glycol, EG, groups) TEGMA71 (three EG groups), OEGMA300x (4.5 in average EG groups) of varying molar masses (MM), and OEGMA50028 (nine in average EG groups) is discussed. Interestingly, the temperature of LLPS (TLLPS) is controlled by the length of the PEG side ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…12 Phase separation and behaviour in the ATPS depend among other factors on polymer concentration, polymer molar mass, pH, and temperature. [13][14][15][16] One key factor for the critical polymer concentration and correspondingly a stable APTS is the molar mass of the used compounds. In recetn years, various studies showed a significant influence of the molar mass to the critical polymer concentration.…”
Section: Introductionmentioning
confidence: 99%
“…12 Phase separation and behaviour in the ATPS depend among other factors on polymer concentration, polymer molar mass, pH, and temperature. [13][14][15][16] One key factor for the critical polymer concentration and correspondingly a stable APTS is the molar mass of the used compounds. In recetn years, various studies showed a significant influence of the molar mass to the critical polymer concentration.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 Dispersity ( Đ ) (molar mass distribution) values vary between 1.10 and 1.20, and agree with previously reported values for copolymers synthesised through GTP and using OEGMA monomers. 57–60…”
Section: Resultsmentioning
confidence: 99%
“…55,56 Dispersity (Đ) (molar mass distribution) values vary between 1.10 and 1.20, and agree with previously reported values for copolymers synthesised through GTP and using OEGMA monomers. [57][58][59][60] . The GPC profile (Figure 2) confirms the successful synthesis of polymer 1 (AB), OEGMA300 16 -b-DMAEMA 32 , and its precursor, with minimal deactivation.…”
Section: Molar Mass and Compositionmentioning
confidence: 99%
“…Furthermore, a great advantage of such polymers is that their LCST can be tuned according to their application requirements. For example, it has been shown that LCST values close to physiological temperatures (i.e., 310 K, ~37 • C) could be achieved by the copolymerization of OEGMA with various hydrophobic monomers [26][27][28][29][30][31][32]. Of the abovementioned polymethacrylates, PTEGMA appears to be a suitable candidate for biomedical applications because its LCST of ~50 • C can be also tuned by copolymerization with hydrophobic monomers; however, its copolymerization and behavior under temperature variations has seldom been explored.…”
Section: Introductionmentioning
confidence: 99%